The importance of the procurement phase in supply chain management for resources (5M) purchase; case study of engineering procurement construction (EPC) project / Farrah Rina Mohd Roshdi, Kharizam Ismail, Norsuzila Lop and Lilawati Ab Wahab - Mohd Roshdi, Farrah Rina; Ismail, Kharizam; Lop, Norsuzila; Ab Wahab, Lilawati (UiTM Cawangan Johor, 2023)
The procurement phase and project management phase are typically dealt with in every construction project. The procurement responsibilities are to purchase following the project 's requirement aligned with contractual agreement involved in the project. The use of machinery, manpower,method ,money, and materials (5M) to complete the job necessitates all of these resources at once in to set up a stable financial cycle. The importance of 5M as resources in procurement to support organizational policy is thus discovered by this study. The literature search on the procurement flow and responsibilities digest from scholars and generates the conceptual framework of Engineering Procurement Construction (EPC) project 's procurement's responsibilities and workflow. Hence, this study was aimed to examine the value of procurement responsibilities for resources purchasing in supply chain management's perspectives specifically in oil and gas fabrication EPC projects as a theoretical framework study. The term procurement appeared in the EPC contract to emphasise that the phase participated not only stages but also the contractual of the project applied. Spending within budget, financial control meeting project value, optimising material usage, and sufficiently matching project goals within contract as for EPC projects as a case study involved million-dollar contract value at different currencies from varies country are important procurement duties that contribute to project control. Keywords: cost control, procurement, resources 5M, supply chain